2018
DOI: 10.1002/jat.3637
|View full text |Cite
|
Sign up to set email alerts
|

Cover Image

Abstract: The cover image, by Wen‐qing Zhu et al., is based on the Research Article Effect of titanium ions on the Hippo/YAP signaling pathway in regulating biological behaviors of MC3T3‐E1 osteoblasts, DOI: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In our previous study, it was found that excessive titanium ions were capable of suppressing osteoblasts growth and inhibiting the osteogenic differentiation via the Hippo/YAP signaling pathway. 36 Changes in the characteristics of titanium surfaces can directly inuence cell adhesion behavior. 37,38 In this study, the decreased adherent MC3T3-E1 cells and poor cell spreading on the Ti-pg and SLA-pg surfaces were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, it was found that excessive titanium ions were capable of suppressing osteoblasts growth and inhibiting the osteogenic differentiation via the Hippo/YAP signaling pathway. 36 Changes in the characteristics of titanium surfaces can directly inuence cell adhesion behavior. 37,38 In this study, the decreased adherent MC3T3-E1 cells and poor cell spreading on the Ti-pg and SLA-pg surfaces were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In male hamsters, quercetin doses of 0.3 or 3 % in the diet (corresponding to around 150 and 1500 mg per kg bw and day, respectively) for around 6 months caused an increase in the number of larger tumors in the kidney (> 5 mm) and an increase in abdominal metastases compared to the estradiol group. [121] The other study with female rats reported especially enhanced cell proliferation and shortening of the tumor latency of mammary glands by quercetin at a dose of 0.25 % in the diet (corresponding to around 150 mg per kg bw) in animals co-treated with estradiol for 8 months compared to the estradiol control group. [122] Both working groups suggested a direct inhibition of the catechol-Omethyltransferase activity by quercetin as a possible mechanism resulting in an elevated formation of the carcinogenic estradiol metabolite 4-hydroxyestradiol and an accompanied reduction of the anti-carcinogenic metabolite 2-methoxyestradiol.…”
Section: Effects On Estrogen-mediated Carcinogenesismentioning
confidence: 99%
“…Most studies revealed no or even chemo-preventive effects of quercetin (details see [30] ). However, a few studies using different carcinogens (N-ethyl-N'-nitro-N-nitrosoguanidin, azoxymethane, nitrosomethylurea or 17β-estradiol) reported also an enhanced tumor development in duodenum, [117] colon, [118] pancreas, [119,120] kidney [121] or mammary glands [122] of rodents after quercetin treatment with 0.2 to 3.4 % in feed (corresponding to approximately 150 to 3400 mg per kg bw and day). Two of these studies started the quercetin treatment in pregnant rats continuing in their offspring and investigated the tumorigenesis in the offspring.…”
Section: Promotion Of Already Existing Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations